Plate 9: Various bottles, receivers, and vessels - Accum, Friedrich Christian (An Explanatory Dictionary of the Apparatus and Instruments Employed in the Various Operations of Philosophical and Experimental Chemistry, 1824)
Depicts assorted bottles (cast iron; gas; with various necks), adopters, pelican, matrass, air jars, compound distillatory apparatus, balloon receivers, and conducting tubes.
Keywords: Chemistry; Chemical apparatus